2020
DOI: 10.1159/000509253
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Periostin Levels and Eosinophils in Nasal Polyps Are Associated with the Preventive Effect of Endoscopic Sinus Surgery for Asthma Exacerbations in Chronic Rhinosinusitis Patients

Abstract: <b><i>Background:</i></b> Eosinophilic nasal polyps (NPs) are associated with the presence of asthma in chronic rhinosinusitis (CRS) patients. Serum periostin has been considered a relevant biomarker for unified airway diseases. <b><i>Objective:</i></b> To determine the utility of biomarkers including serum periostin that reflects reduction of exacerbations of comorbid asthma in CRS patients. <b><i>Methods:</i></b> We prospectively recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In a study by Kanemitsu et al . , serum periostin levels did not decrease at month 12 in 7 CRS patients who experienced recurrence after ESS and the authors stated that NP recurrence could be reflected by the change in serum periostin levels after ESS [ 32 ]. As a result of their study with 338 CRS patients, of which 278 had CRSwNP, Oka et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kanemitsu et al . , serum periostin levels did not decrease at month 12 in 7 CRS patients who experienced recurrence after ESS and the authors stated that NP recurrence could be reflected by the change in serum periostin levels after ESS [ 32 ]. As a result of their study with 338 CRS patients, of which 278 had CRSwNP, Oka et al .…”
Section: Discussionmentioning
confidence: 99%
“…The link between chronic rhinosinusitis and asthma is well-established, and it seems that olfactory dysfunction in the presence of asthma indicates similar inflammatory mechanisms in both the upper and lower airways. Kanemitsu et al [28] showed that sputum eosinophilia in asthmatic chronic rhinosinusitis patients was associated with olfactory dysfunction, which suggests that this impairment is a potential indicator of Th2-driven inflammation of the lower airways. In addition, although there were no such patients in the present study, it seems that a diagnosis of bronchiectasis may also be associated with chronic rhinosinusitis and olfactory loss [29].…”
Section: Discussionmentioning
confidence: 99%